TEACHING ETHICS IN ACCOUNTING: APPROACHES AND CHALLENGES - Shahida Bt Shaharuddin; Nurul Nazlia Jamil (Journal of Islamic, Social, Economics and Development, 2022)
This paper aims to review the literature that discussing on the teaching approaches used in teaching ethics courses, especially in the accounting field. This paper also highlights the challenges associated with the teaching approaches. Given the influence of ethics education on the ethical behavior of students, it is important to ensure the quality of ethics courses offered in the university. One of the criteria that determines quality is by looking at its pedagogy. It is vital to set the objectives of the course before determine the teaching approaches. The goal of the ethics course is to develop moral awareness and moral sensitivity for the students. Due to this, previous literature suggests accounting educators use active learning for teaching approaches in the ethics course. This includes case studies, guest speakers, and group discussions. Group discussions can be conducted using activities such as role-playing. However, there are challenges in using active learning in the pedagogy. The challenges are time limitation, students’ participation, and creating a safe learning environment. This paper can help accounting educators to get ideas on appropriate teaching approaches in an ethics course.